Preliminary results of the degradation of platinum based catalyst in PEM fuel cells using PIXE - Gunther, Maria Virginia; Debray, Mario Ernesto; Corti, Horacio Roberto (International Atomic Energy Agency, 2012)
Fil: Gunther, Maria Virginia. Comisión Nacional de Energía Atómica; Argentina